2017
DOI: 10.1002/oby.21846
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss in Weight Watchers Online with and without an activity tracking device compared to control: A randomized trial

Abstract: WWO produced significantly more weight loss at 3 months relative to Control, but not at 12 months. Significantly more WWO than Control participants lost ≥ 5% at both 3 and 12 months. Participants receiving an activity tracking device did not achieve greater weight loss or physical activity increases than those in a Control condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 32 publications
2
78
1
Order By: Relevance
“…Each study population consisted of overweight and obese adults with sample sizes ranging from 38 to 15,310. Inter-ventions varied widely, with different types of apps and wearables tested, multiple conditions implemented (Burke et al, 2011; Jakicic et al, 2016; Spring et al, 2017; Svetkey et al, 2015; J. G. Thomas et al, 2017; Turner-McGrievy et al, 2017), and elements such as coaching (Svetkey et al, 2015; Toro-Ramos et al, 2017), nutrition education (Burke et al, 2011; Toro-Ramos et al, 2017), website integration (Godino et al, 2016; Jakicic et al, 2016), and group sessions (Siriwoen et al, 2018; Spring et al, 2017) incorporated that differed from study to study.…”
Section: Resultsmentioning
confidence: 99%
“…Each study population consisted of overweight and obese adults with sample sizes ranging from 38 to 15,310. Inter-ventions varied widely, with different types of apps and wearables tested, multiple conditions implemented (Burke et al, 2011; Jakicic et al, 2016; Spring et al, 2017; Svetkey et al, 2015; J. G. Thomas et al, 2017; Turner-McGrievy et al, 2017), and elements such as coaching (Svetkey et al, 2015; Toro-Ramos et al, 2017), nutrition education (Burke et al, 2011; Toro-Ramos et al, 2017), website integration (Godino et al, 2016; Jakicic et al, 2016), and group sessions (Siriwoen et al, 2018; Spring et al, 2017) incorporated that differed from study to study.…”
Section: Resultsmentioning
confidence: 99%
“…It remains unclear for each type of self‐monitoring how much the link between adherence and weight loss can be explained by underlying level of motivation or self‐regulation ability. Experimental research that has manipulated the provision or prescription of digital self‐monitoring tools and examined the resulting effect on weight loss has yielded mixed results . Additional experimental research is needed to determine the extent to which each type of digital self‐monitoring directly improves weight loss and, if there is a causal relationship, identify the specific mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…However, the few other studies published to date have reported limited benefits. For example, we recently conducted a study of WWO with and without a physical activity tracking device and associated online resources for physical activity goal setting and feedback . There was no indication that the tracking technology improved physical activity or weight loss outcomes.…”
Section: Discussionmentioning
confidence: 99%